2008
DOI: 10.1111/j.1442-2042.2007.01924.x
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct carcinoma with acquired cystic disease of the kidney in a long‐term hemodialysis patient

Abstract: Abstract:We report a very rare case of collecting or Bellini duct carcinoma (CDC) found in a 60-year-old male who had received hemodialysis therapy for 21 years. Screening with ultrasonography revealed a solid tumor originating from the cyst wall in the right kidney with acquired cystic disease of the kidney. Subsequent computed tomography (CT) and angiography could not detect another renal tumor. Right radical nephrectomy was performed. The tumor detected preoperatively was composed of papillary renal cell tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…86 The spectrum of renal tumors associated with end-stage renal disease is quite varied and in single cases and small series clear cell renal cell carcinomas, papillary renal cell carcinomas, chromophobe renal carcinoma, collecting-duct carcinoma, tubulocystic carcinoma, angiomyolipoma, oncocytoma and mixed epithelial and stromal tumor have been reported. [87][88][89][90][91][92][93][94] In up to 70% of cases more than one tumor was present in a single kidney. 95 In a detailed study of 66 tumor-bearing kidneys from patients with end-stage renal disease, a wide spectrum of renal neoplasia was noted.…”
Section: Carcinoma Associated With End-stage Renal Diseasementioning
confidence: 99%
“…86 The spectrum of renal tumors associated with end-stage renal disease is quite varied and in single cases and small series clear cell renal cell carcinomas, papillary renal cell carcinomas, chromophobe renal carcinoma, collecting-duct carcinoma, tubulocystic carcinoma, angiomyolipoma, oncocytoma and mixed epithelial and stromal tumor have been reported. [87][88][89][90][91][92][93][94] In up to 70% of cases more than one tumor was present in a single kidney. 95 In a detailed study of 66 tumor-bearing kidneys from patients with end-stage renal disease, a wide spectrum of renal neoplasia was noted.…”
Section: Carcinoma Associated With End-stage Renal Diseasementioning
confidence: 99%
“…1,3,[17][18][19][20][21][22][23][24][25] From these publications it was suggested that clear cell carcinoma, papillary carcinoma and chromophobe carcinoma were the tumour types found, with papillary renal carcinoma over-represented in this group of patients in comparison with the general population. Oncoytoma, 20,[26][27][28][29][30] collecting duct carcinoma 31 and sarcomatoid renal carcinoma 14,32,33 have all been described mostly as isolated cases. Recent data have challenged this view and supported the existence of two tumour types specific to end-stage renal failure (ESRF) and ACKD patients.…”
Section: Pathology Of Renal Carcinoma Associated With Ackdmentioning
confidence: 99%
“…Since December 2006 two of the seven patients have died of the disease. Case 2 was spindle cell carcinoma and case 3 was Bellini duct carcinoma with lymph node metastasis 10 . Since the prognosis of RCC in dialysis patients have been reported as being equivalent to that of sporadic RCC, 9 attending physicians should examine dialysis patients with suspicion of RCC bearing in mind that life‐threatening aggressive cancer can arise.…”
Section: Discussionmentioning
confidence: 99%